Chronobiology and Obesity - Garaulet, Marta; Ordovás, Jose M. (Springer New York : Imprint: Springer, 2013)
Circadian rhythms are such an innate part of our lives that we rarely pause to speculate why they even exist. Perhaps this is the reason why in the medical practice the circadian variability of hormones, metabolites, physiological behaviors or the relevance of time in the presence or absence of different pathologies, have been practically ignored in the past. Some studies have suggested that the disruption of the circadian system may be cause for obesity and manifestations of Metabolic Syndrome (MetS). Shift-work, sleep-deprivation and bright-light-exposure at night are related to increased adiposity (obesity) and prevalence of MetS. Chronobiology and Obesity examines recent advances that have led to researchers to find the relevant link which exists between chronobiology and obesity, but, as it is emphasized throughout the book, there is much more that needs to be explored between the connection.